Virtual Reality in Urban Mobility Projects – Case Study of Passo Fundo-RS - Pedott, Georgea Marthina; Silva, Thaísa Leal da (Technical and Scientific Journal Green Cities, 2024)
Urban mobility is associated with urban transport, as it seeks to meet people's travel needs to carry out daily activities. In this context, promoting the use of active transport to the detriment of automobile use is an important strategy in the search for more sustainable urban mobility, which makes the use of bicycles as a mode of transport more effective. In this scenario, digital technologies, such as Virtual Reality, can be important allies in supporting analyzes and studies on urban mobility.  This article aims to analyze how Virtual Reality can help in the development of urban mobility projects, more specifically in the adaptation of a cycle path in the city of Passo Fundo-RS. In the methodology, initially a bibliographical research was carried out, followed by a data collection with measurements and photographs of four sections of a cycle path in Passo Fundo-RS. Next, the images were modeled, including proposals for improvements to these sections, and finally, an evaluation of the propositions using Virtual Reality glasses and the application of an evaluative questionnaire. To prepare the proposals, elements such as lane protection, signage, the state of conservation of the cycle path, among others, were analyzed. The results regarding both the propositions and the use of Virtual Reality to analyze them were quite satisfactory. Thus, the potential of using Virtual Reality for the development of mobility and urban projects, as well as for analyzing user satisfaction, can be seen.
Keywords: Urban mobility; Active Mobility; Bike lane; Virtual Reality